2013
DOI: 10.1002/asl2.407
|View full text |Cite
|
Sign up to set email alerts
|

Response of oceanic cyclogenesis metrics forNARGIScyclone: a case study

Abstract: In this study, variability of two oceanic cyclogenesis metrics, tropical cyclone heat potential (TCHP) and effective oceanic layer for cyclogenesis (EOLC) in the Bay of Bengal (BoB) during NARGIS cyclone is investigated. EOLC represents the geopotential thickness of near surface stratified layer forms because of the spread of low salinity waters due to fresh water influx from rivers and precipitation. Climatological fields of TCHP and EOLC reveal that NARGIS translated towards the region of higher EOLC as seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…initial intensity of cyclone, thermodynamic state of atmosphere through which the cyclone propagates and finally the heat exchange with the upper layer of the ocean underlying the core of the cyclone. Rapid intensification of TC is noticed when it passes over the deep upper ocean mixed layer and that upper ocean thermal structure plays a significant role in the intensification process [32][33][34]. Sutyrin [35] performed simulations with a coupled model of the oceanic and atmospheric boundary layers and concluded that the interaction is strong enough to change the supply of heat and moisture fluxes from the ocean into the atmosphere significantly within few hours of the formation of the storm and consequently, influence the TC intensity.…”
Section: Role Of Ocean In Genesis and Intensificationmentioning
confidence: 99%
“…initial intensity of cyclone, thermodynamic state of atmosphere through which the cyclone propagates and finally the heat exchange with the upper layer of the ocean underlying the core of the cyclone. Rapid intensification of TC is noticed when it passes over the deep upper ocean mixed layer and that upper ocean thermal structure plays a significant role in the intensification process [32][33][34]. Sutyrin [35] performed simulations with a coupled model of the oceanic and atmospheric boundary layers and concluded that the interaction is strong enough to change the supply of heat and moisture fluxes from the ocean into the atmosphere significantly within few hours of the formation of the storm and consequently, influence the TC intensity.…”
Section: Role Of Ocean In Genesis and Intensificationmentioning
confidence: 99%